Samorealizacja – potencjał dziecka w twórczości plastycznej. Propozycja programu kształcenia plastycznego w klasach początkowych - Urszula Szuścik (Problemy Wczesnej Edukacji)
The article presents a proposal for the development of the creative and artistic potential of a child in early school age. Potential is treated by the author as discovering the possibilities and abilities that, thanks to the conditions and atmosphere in the education process, a child develops and shapes. This is related to the issue of creativity and self-realization through creative activities, with discovering and exceeding one’s abilities in the course of the creative educational process. The education of a child should go towards the development of his creativity, understood as shaping a person who is integrated in the cognitive, emotional and operational spheres. A free person, independent in making decisions, valued, without a sense of guilt. The result is the development of the child’s natural abilities and skills, and thus its potential mental strength in current activities. Based on research, including her own, the author presents a proposal for the development of a child’s creative potential in the field of art based on the education of his visual perception.